The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1248/jhs.49.239
|View full text |Cite
|
Sign up to set email alerts
|

Negative Correlation between Urinary Selenium and Arsenic Levels of the Residents Living in an Arsenic-Contaminated Area in Bangladesh

Abstract: Toxicological and metabolic interactions of selenium (Se) with arsenic (As) have been reported in many experimental studies. However, for human populations, possible interactions between As and Se and their toxicological significance have not been established. In this study, we have examined the relationship between Se and As in spot urine samples collected from the inhabitants of two rural communities of northeast Bangladesh. The urinary As (U As ) and Se (U Se ) concentrations were determined by hydride gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
(9 reference statements)
1
8
0
Order By: Relevance
“…It has been reported that selenium may act as an antagonist to arsenic. Furthermore, selenium dietary supplements were found to significantly decrease the arsenic body load [14,23]. In our study, we found normal ranges of selenium concentration with quite similar median values of 125 μg/L for the control and 113 μg/L for the northern inhabitants, respectively.…”
Section: Resultssupporting
confidence: 70%
“…It has been reported that selenium may act as an antagonist to arsenic. Furthermore, selenium dietary supplements were found to significantly decrease the arsenic body load [14,23]. In our study, we found normal ranges of selenium concentration with quite similar median values of 125 μg/L for the control and 113 μg/L for the northern inhabitants, respectively.…”
Section: Resultssupporting
confidence: 70%
“…It is not clear whether this is due to: (i) the free-radical scavenging nature of Se compounds; (ii) Se directly affecting As metabolism, perhaps through altering As methylation [68];or through the direct formation of As-Se compounds, such as seleno-bis (S-glutathionyl) arsinium [69]; or (iii) excretion patterns [70].…”
Section: Reviewmentioning
confidence: 99%
“…Arsenic also causes anemia (ATSDR 2007;Parish et al 1979), the severity of which indicates the extent of disruption to normal regulatory mechanisms exerted by macrophages and T-cells (Sathe et al 1990;Bogner et al 1990;Gascon et al 1993); and it also acts as an antagonist to selenium (Se), affecting its metabolism in vivo (Miyazaki et al 2003;Schrauzer 1987).…”
Section: Health Importance Of Arsenicmentioning
confidence: 99%